490 Sex-based differences in seat-belt use across Africa, South Asia, and South America. (20th November 2022) - Suresh, Rachana; Zia, Nukhba; Shah, Janavi; Bachani, Abdulgafoor M
Abstract : Background: Use of seatbelts have been shown to decrease severity of injury and risk of fatality from road traffic crashes. However, there is a lack of evidence regarding sex-based differences in seatbelt use in LMICs. Aims: The aim of this study was to characterize sex-based differences in seatbelt use among motor vehicle users in LMICs. Methods: This study involved secondary analysis of cross-sectional data collected from ten cities- Accra, Addis Ababa, Bandung, Bangkok, Ho Chi Minh city, Mumbai, Shanghai, São Paulo, Bogota, and Fortaleza, from 2015 to 2019, by Johns Hopkins International Injury Research Unit (IIRU). Descriptive analyses were performed after stratifying both drivers and passengers based on sex. Discrete variables were assessed as percentages. Comparison between groups was performed using a Chi-squared test. Logistic regression models were used to study the association between seatbelt use and sex. Results: A total of 2, 801, 131 individuals were observed. Overall prevalence of seatbelt use among all occupants was 64.8%. Seatbelt use was higher among female drivers (91.5%) compared to male drivers (83.2%) (p-value<0.001). On adjusted analyses, female drivers were 7% more likely to wear a seatbelt compared to male drivers (p-value<0.0001). Among passengers, seatbelt use was higher among females (35.6%) compared to males (26.9%) (p-value<0.001). On adjusted analyses, female passengers were 5% more likely to wear a seatbelt compared to male passengers (p-value<0.0001). Conclusions: Female drivers and passengers are more likely to use seatbelts than their male counterparts.